PENGARUH PENGGUNAAN ELASTIC BANDAGE BERMOTIF (STIKER) TERHADAP TINGKAT KOOPERATIF ANAK USIA PRA SEKOLAH SELAMA PROSEDUR INJEKSI IV (INTRA VENA) PERSET - I Ketut Arta Agus Wiguna; Francisca Shanti Kusumaningsih; Made Sumarni (Coping: Community of Publishing in Nursing, 2015)
Abstract, Elastic bandage patterned (sticker) is one of the atraumatic care aplication that modified the environment to increase the children’s comfort level during hospitalization. The hospitalized pre-school children who inserted intravenous fluid drop line may become more comfortable with elastic bandage patterned (sticker) as fixation so that children will be cooperative towards action, especially on intravenous (IV) perset injection. The cooperative levels on  the pre-school children was observed using observation sheet. Methode: Quasi-experimental research  with post-test only non equivalent control group design. The purpose of study to investigate the effects of elastic bandage patterned (sticker) usage on the pre-school children’s cooperative levels during IV perset injection procedure. The number of sample in this study is 30 that were chosen by purposive sampling technique and divided into control groups and intervention groups. The observation data were analyzed using chi square test and the result of  significant differences in the level of cooperative control group and the intervention group is p value = 0.008 (? ? 0,05) and earned value OR = 13. The result of this study conclude that bandage patterned is effected on the pre-school age children’s cooperative levels during IV perset injection procedure which inervention  group has 13 times higher in possibilty for cooperative behaviour. Further research in order to control other variables that could affect the results of the study as support for parents and private of children.